2014
DOI: 10.1016/j.pediatrneurol.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Structural Reorganization of the Corticospinal Tract in Children With Sturge-Weber Syndrome

Abstract: Background Reorganization of the corticospinal tract (CST) after early damage can limit motor deficit. In this study, we explored patterns of structural CST reorganization in children with Sturge-Weber syndrome. Methods Five children (age 1.5-7 years) with motor deficit due to unilateral Sturge-Weber syndrome were studied prospectively and longitudinally (1-2 years follow-up). CST segments belonging to hand and leg movements were separated, and their volume was measured by diffusion tensor imaging (DTI) trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
(33 reference statements)
2
12
1
Order By: Relevance
“…The population in the present study had a wider age range (1-20 years vs. 1-14 years in the previous study), and non-linear fitting of normalized volumes demonstrated, for the first time, an early CST-specific age-related increase in both hand and leg motor segments which reached their maxima around age 5-6 years, followed by a sharp decline in the next 5-6 years of age, and subsequently a flattening out after adolescence. Similar to our previous findings [16], the age-related correlations were the strongest in the right leg-related CST segments. However, the curves showed a similar pattern (although with weaker correlations) in the hand segments, and, to the least degree, in the left leg segment as well.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The population in the present study had a wider age range (1-20 years vs. 1-14 years in the previous study), and non-linear fitting of normalized volumes demonstrated, for the first time, an early CST-specific age-related increase in both hand and leg motor segments which reached their maxima around age 5-6 years, followed by a sharp decline in the next 5-6 years of age, and subsequently a flattening out after adolescence. Similar to our previous findings [16], the age-related correlations were the strongest in the right leg-related CST segments. However, the curves showed a similar pattern (although with weaker correlations) in the hand segments, and, to the least degree, in the left leg segment as well.…”
Section: Discussionsupporting
confidence: 91%
“…The use of both absolute and normalized CST volumes provided a more comprehensive insight into normal CST maturation; although normalized volumes are affected by whole-brain changes, they have the advantage of providing data more specific for CST after taking out the effect of global white matter variations. Therefore, these data refine our recent results demonstrating an age-related decrease of right CST leg segments in children with normal motor functions [16]. The population in the present study had a wider age range (1-20 years vs. 1-14 years in the previous study), and non-linear fitting of normalized volumes demonstrated, for the first time, an early CST-specific age-related increase in both hand and leg motor segments which reached their maxima around age 5-6 years, followed by a sharp decline in the next 5-6 years of age, and subsequently a flattening out after adolescence.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Contralateral changes have been also documented by FDG‐PET in the form of increased cortical metabolism, mostly affecting posterior regions including the visual cortex 12, 13, 14. In addition, DTI fiber tractography studies showed signs of strengthening of the contralateral central motor and visual pathways in some SWS children with preserved motor and visual functions, respectively 13, 15…”
Section: Discussionmentioning
confidence: 99%